1975
DOI: 10.1143/jjap.14.1987
|View full text |Cite
|
Sign up to set email alerts
|

Emission Properties of Two-Photon Pumped InSb Laser under Magnetic Field

Abstract: The magnetic tuning characteristics of InSb laser pumped by a TE CO2. laser were studied.The tuning characteristic depended on the carrier density of n-InSb sample. For a sample with low carrier density, the emission energy shifted monotonously to higher energy with increasingmagnetic field and only one linear shift varying as Δε=(\hbarωc-|gc|βH)/2 was o bserved at a high magnetic field. For a sample with high carrier density, the emission energy shifted to lower energy at a low magnetic field, and at a high m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1979
1979
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In practice, the earliest two-photon pumped (2PP) lasing was observed during the 1960s−1970s in several semiconductor crystals operating at low temperature. Also, there were a few papers reporting two-photon excited stimulated emission in gas and metal vapor systems during the 1970s−1990s. On the other hand, between the 1970s and 1993, there were several experimental reports on two-photon excited stimulated emission for commercial organic dye systems. In these cases with no cavity enhancement, most of the observed output was the so-called amplified spontaneous emission (ASE) that usually was only characterized by spectral narrowing, not by high directionality. In 1995, He et al reported 2PP cavity lasing with a narrow spectral line width and high directionality for solutions of a novel dye and for doped solid matrixes …”
Section: 11 General Features Of Mpp Lasing Materials and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the earliest two-photon pumped (2PP) lasing was observed during the 1960s−1970s in several semiconductor crystals operating at low temperature. Also, there were a few papers reporting two-photon excited stimulated emission in gas and metal vapor systems during the 1970s−1990s. On the other hand, between the 1970s and 1993, there were several experimental reports on two-photon excited stimulated emission for commercial organic dye systems. In these cases with no cavity enhancement, most of the observed output was the so-called amplified spontaneous emission (ASE) that usually was only characterized by spectral narrowing, not by high directionality. In 1995, He et al reported 2PP cavity lasing with a narrow spectral line width and high directionality for solutions of a novel dye and for doped solid matrixes …”
Section: 11 General Features Of Mpp Lasing Materials and Devicesmentioning
confidence: 99%
“…In practice, the earliest two-photon pumped (2PP) lasing was observed during the 1960s-1970s in several semiconductor crystals operating at low temperature. [380][381][382][383][384] Also, there were a few papers reporting two-photon excited stimulated emission in gas and metal vapor systems during the 1970s-1990s. [385][386][387][388][389][390] On the other hand, between the 1970s and 1993, there were several experimental reports on two-photon excited stimulated emission for commercial organic dye systems.…”
Section: General Features Of Mpp Lasing Materials and Devicesmentioning
confidence: 99%
“…It has been employed in this capacity by a number of workers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) because it is chemically compatible with SiC and can be obtained in single-crystal form in ultrahigh purities at reasonable cost. It has been employed in this capacity by a number of workers (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) because it is chemically compatible with SiC and can be obtained in single-crystal form in ultrahigh purities at reasonable cost.…”
Section: Thermal Stresses In Heteroepitaxial Beta Silicon Carbide Thimentioning
confidence: 99%
“…There are two major mechanisms that primarily responsible for this phenomenon. One is based on sequential stepwise multiphoton excitation in materials such as rare-earth doped crystals, inorganic glasses and optical fibers. The second process is initiated by a direct simultaneous two-photon absorption and subsequent population inversion and has been observed in semiconductor and rare earth crystals, dye solutions, and dye-doped solid matrixes. In this work, the two-photon induced population inversion of GFP is further investigated and the characteristics of the ultrafast two-photon pumped lasing of GFP are presented. Parameters such as the spectral output, laser threshold and output-input energy characteristics are given and compared to theoretical results.…”
Section: Introductionmentioning
confidence: 99%
“…One is based on sequential stepwise multiphoton excitation in materials such as rare-earth doped crystals, inorganic glasses and optical fibers. [10][11][12][13][14][15][16][17][18] The second process is initiated by a direct simultaneous two-photon absorption and subsequent population inversion and has been observed in semiconductor and rare earth crystals, [19][20][21][22] dye solutions, and dye-doped solid matrixes. [23][24][25][26][27][28][29] In this work, the two-photon induced population inversion of GFP is further investigated and the characteristics of the ultrafast two-photon pumped lasing of GFP are presented.…”
Section: Introductionmentioning
confidence: 99%